Features of the power-law fluid over cylinders in a channel via gap aspects: Galerkin finite element method (GFEM)-based study - Faraz, Naeem; Majeed, Afraz Hussain; Mehmood, Asif; Sajad, Haseeba; Khan, Y. (Frontiers in Physics, 2023)
The goal of this investigation is to carry out a comprehensive analysis of hydrodynamic forces, with particular attention being paid to the power-law fluid flow across cylinders and presence gap considerations. With the assistance of the Galerkin finite element method (GFEM), the discretization of the two-dimensional system of non-linear partial differential equations was successfully completed. The research is carried out with a significant variance of the flow behavior index n from .3 to 1.7, gap aspects Gp from 0 .0 to .3, and fixed Reynolds number Re 20. To obtain an extremely accurate solution, first, a coarse hybrid computational mesh needs to be developed, and then, more refinement must take place. The selection of the best possible case can be determined by comparing flow patterns, coefficients of drag and lift, and cylinder gaps. The shear-thickening behavior of fluids has a substantially greater influence on the drag characteristics than either the Newtonian or the shear-thinning behavior of fluids do. In addition to this, the shear-thickening action causes the upstream obstacle’s drag coefficient to increase because the gap spacing becomes more widespread.